Diseño y evaluación de una estrategia didáctica para enseñar a preguntar - Chamizo-Guerrero, José Antonio; Ríos-López, Griselda (Revista Científica, 2017)
In this paper, after a literature review it was characterized the questions in open and closed. Later a teaching strategy that allows high school students learn to ask open-ended questions was designed. The strategy included lectures, experiments and visits. Finally we carried out an intervention with various groups. The results show that it is possible to teach to ask open-ended questions, those that characterize scientific thinking skills.